2017
DOI: 10.4172/2168-9601.1000223
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Brand Awareness on the Consumers’ Purchase Intention

Abstract: This paper presents a review about the impact of brand equity and brand awareness on the purchasing intentions of the consumers. The purpose of the paper is to elaborate the relation between the awareness of a brand and the intention of consumer of buying that brand. This has been done by going through different literature and articles by different authors. It will help the readers to come across the work done by various well known authors at one place and hence will help to know how knowing a brand well will … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
1
16

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(134 citation statements)
references
References 9 publications
6
66
1
16
Order By: Relevance
“…The same result was figured out by Keh and Xie (2008), Lafferty et al (2002), Oztamur and Karakadılar (2014), See-To and Ho (2014) and Muntinga et al (2011). Finally, the results showed that brand loyalty significantly affected customer purchase intention (Calvo-Porral et al, 2015;Chen et al, 2016;Chi et al, 2009;Pandey & Srivastava, 2016;Malik et al, 2013;Al-Tit & Nakhleh;Shahid et al, 2017). For organizations to start an effective application, five antecedents should be considered: corporate reputation, social media frequency updates, content of social media, social media motivations and brand communications.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The same result was figured out by Keh and Xie (2008), Lafferty et al (2002), Oztamur and Karakadılar (2014), See-To and Ho (2014) and Muntinga et al (2011). Finally, the results showed that brand loyalty significantly affected customer purchase intention (Calvo-Porral et al, 2015;Chen et al, 2016;Chi et al, 2009;Pandey & Srivastava, 2016;Malik et al, 2013;Al-Tit & Nakhleh;Shahid et al, 2017). For organizations to start an effective application, five antecedents should be considered: corporate reputation, social media frequency updates, content of social media, social media motivations and brand communications.…”
Section: Discussionsupporting
confidence: 56%
“…Moreover, Chi, Yeh and Yang (2009) found a positive impact of brand loyalty on customer purchase intention. The same finding was echoed in many studies (Calvo-Porral, Martínez-Fernández, Juanatey-Boga, & Lévy-Mangín, 2015; Chen, Chen, & Lin, 2016;Malik, Ghafoor, & Iqbal, 2013;Shahid, Hussain, & aZafar, 2017). Consequently, the following hypothesis was added: H6: Brand loyalty significantly affects purchase intention.…”
Section: Figure 3 Hypotheses 1-5 Brand Loyalty and Customer Purchasementioning
confidence: 70%
“…By maintaining this performance, consumers will remain loyal to the Golden Farm brand and repurchase the product in the future (Kamal et al, 2019). Brand loyalty will provide many benefits for the company, such as consumers will recommend the product to others, so that in the end, it can reduce marketing costs (Shahid et al, 2017). Loyal consumers will not switch to other brands.…”
Section: Discussionmentioning
confidence: 99%
“…Para responden yang masuk dalam kategori top of mind merupakan responden yang sudah pernah menggunakan layanan kesehatan tersebut (Nugroho, 2013) dan kemungkinan karena mereka memang belum pernah berkunjung ke rumah sakit lain selain klinik laktasi di RSML (Rimiyati & Astutu, 2012). Menurut penelitan yang dilakukan oleh Shahid et al (2017) bahwa konsumen akan membeli sebuah produk yangsudah mereka ketahui dan kenali dengan baik.…”
Section: Pembahasan Hubungan Brand Awareness Dengan Keputusan Pemanfaunclassified